2021
DOI: 10.1021/acs.jafc.1c01478
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Diastereomeric Dihydromenthofurolactones by Cystostereum murrayi and Aroma Dilution Analysis Based on Dynamic Headspace Extraction

Abstract: Submerged cultures of the basidiomycota Cystostereum murrayi emit an intensive coconut-like, sweetish, and buttery smell. For identification of the key aroma compounds, an aroma dilution analysis using dynamic headspace was performed by adjusting the split ratio of the GC inlet system. Flavor dilution (FD) factors varied from 22 up to ≥218, whereby the largest class of compounds represented terpenoids, including two rare stereoisomers of 3,6-dimethyl-2,3,3a,4,5,7a-hexahydrobenzofuran (dill ether, ee ≥ 99.9). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…The biosynthesis of these monoterpene ethers as well as of wine lactone (39, FD 2048) by PSA has been reported by Trapp et al, who have shown that these benzofuranoid compounds were formed de novo by the fungus from D-glucose [14]. The biosynthesis of dill ether has also been reported for the fungus Cystostereum murrayi recently [31].…”
Section: Aroma Extract Dilution Analysis and Compound Identificationmentioning
confidence: 73%
“…The biosynthesis of these monoterpene ethers as well as of wine lactone (39, FD 2048) by PSA has been reported by Trapp et al, who have shown that these benzofuranoid compounds were formed de novo by the fungus from D-glucose [14]. The biosynthesis of dill ether has also been reported for the fungus Cystostereum murrayi recently [31].…”
Section: Aroma Extract Dilution Analysis and Compound Identificationmentioning
confidence: 73%
“…As the investigated sample was solid, the DHS ADA technique, developed by Brescia et al for liquid samples, was first validated using a model system. 22 The split vents of TDU and CIS were sequentially combined to dilute the sample without the use of solvents. Linear correlations of the SR with the peak area of the EIC were shown for linalool, methyl anthranilate, and thymol (Figure 5A) as well as for (E)-, (Z)-linalool oxide, benzaldehyde, and geraniol (Supporting Information Figure S1A).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Apart from this, it is an easy, quick, solvent-free, and targeted tool for flavor analysis. 22 It allows for the simultaneous extraction of terpenes and aromatic compounds, for example, 2-aminobenzaldehyde.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations